Business models for the circular economy : opportunities and challenges for policy. (OECD Publishing, 2019)
Natural resources, and the materials derived from them, represent the physical basis for the economic system. Recent decades have witnessed an unprecedented growth in demand for these resources, which has triggered interest from policy makers in transitioning to a more resource efficient and circular economy. This report presents a typology of five circular business models that could support the transition to a more resource efficient and circular economy: circular supply, resource recovery, product life extension, sharing, and product service system models. It reviews the current market penetration and assesses the potential scalability of each business model. Environmental potential is also discussed, as well as risks and unintended consequences that could result from a more widespread adoption of these business models. The report provides a broad set of policy approaches that could help alleviate some of the barriers that currently hinder the widespread adoption of circular business models.